Funcionarios Centro de Planificación y Programación Institucional. (UNED, 2025)
En el orden usual: Juan Carlos Parreguirre, César Sancho, Alvaro García, Elián Valerio, Zaira Flores, Heidy Rosales, Ileana Piedra, Ana Iveth Rojas